Hukum Islam Dan Peradaban: Perspektif Sejarah, Filsafat, Dan Sosiologi - Aminudin (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Babunnajah Pandeglang, 2024)
This article examines the relationship between Islamic law and civilisation from three main perspectives: history, philosophy and sociology. Historically, Islamic law has played an important role in the formation and development of Islamic civilisation since its early days. Islamic law not only regulates spiritual and ritual aspects, but also includes social, political and economic dimensions. Islamic law contributed to building classical Islamic civilisation, including in the fields of education, economics, politics, culture and science. From a philosophical perspective, Islamic law has a strong philosophical foundation, rooted in the Islamic worldview and basic religious principles, such as tawhid, maqasid al-syariah, and the relationship between revelation and reason. Islamic law is also closely linked to ethics in the context of civilisation. In addition, the flexibility and adaptability of Islamic law in the face of changing times is an important philosophical discussion. The development of science and technology also has implications for Islamic law. Sociologically, Islamic law affects family, educational, and economic institutions in Muslim societies. Social dynamics in the implementation of Islamic law in different countries and cultures show a diversity of interpretations and practices. The application of Islamic law in the modern era also faces various sociological challenges, such as contemporary issues and rapid social change.This multidisciplinary study demonstrates the interrelationship between the perspectives of history, philosophy and sociology in comprehensively understanding Islamic law and civilisation. The findings of this study provide important lessons and implications for the future development of Islamic law that is more responsive to the challenges of the times. Suggestions for further research and development of Islamic law are also given, such as more in-depth historical studies, empirical research on the implementation of Islamic law, interdisciplinary approaches, and the development of contextualised ijtihad methodologies.